Boundaries for use in wheat variety classification use in Australia - Williams, Richard Malcolm (Curtin University, 2006)
Suppliers of wheat must ensure that their products have the required quality profile demanded by customers and consistently deliver that quality in order to be competitive. Australia’s wheat industry is highly exposed to such competitive threats because it relies heavily on exports. An integral component in maintaining Australia’s competitiveness has been its classification system. The first step involves the complex process of determining a genotypic quality profile of each variety – a variety classification. At harvest, subsequent steps are the use of a statutory declaration and testing of physical quality traits. Together these steps determine how deliveries of wheat are segregated. A single variety can have different classifications across the 7 classification regions of Australia. Most classification regions are divided along state borders and these are not reflective of potential environmental influences.The manner in which Australia wheat breeding programs now tackle their task has changed since 1999. The commercially focused companies of the current era have national targets to remain viable, and are focused on costs. Other evolutions associated with the change, are the introduction of different sources of parental material, and moving to more economic composite quality testing regimes instead of the individual site by site testing used in the past. Together, these factors, particularly variety adaptability and stability of performance, have the capacity to increase variability. The likelihood of variation is further increased given that the current classification regions upon which classification decisions are made do not adequately reflect environmental effects on the expression of quality. To determine whether better divisions of the Australian wheat-belt could be identified for variety classification purposes, a substantial spatial and temporal database of historical quality results was assembled. The creation of this relational database was unique, because never before had expansive sets of independent, state-based, quality sub-sets been joined together. However, the data were unbalanced and required alternative statistical tools to be analysed. The relational database was the platform from which three phases of research were conducted.The first research phase investigated the extent of cross over, or re-ranking of results, statistically referred to as genotype x environment interaction. The approach was to assess balanced data sets, in a manner reminiscent of the most common method identified from the literature. The results of those analyses showed that the size of genotype and environment interaction was small compared with the main effects of genotype and environment. The second phase of research focused on identifying alternative boundaries for classification purposes. Test divisions were compared with the current set of 7 classification regions for the capacity to minimise environmental variance while maintaining differences between the zones of a set. Test divisions were based on fourteen published divisions of the Australian wheat-belt. Analyses were conducting using residual maximum likelihood because of the unbalanced structure of the data. Estimates of variance components, quality trait means and standard errors were calculated. Consideration of such estimates resulted in the identification of 4 different divisions of the wheat-belt that had low environmental variance levels for important quality traits such as maximum resistance, dough development time, and water absorption.In addition, these 4 divisions of the wheat-belt had fewer number of zones compared with the existing set of classification regions because they linked separate parts of the wheat-belt together. In order of decreasing merit, the 4 divisions of the wheat-belt represented average October maximum temperatures; agro-ecological zones reported by Williams et al. (2002); average annual rainfall; and Departments of Agriculture recommendation zones. A final phase of crosschecking was performed to assess the veracity of the 4 identified divisions. A cluster analysis supported the orientation of their boundaries and it was also observed that the use of fixed boundaries for classification purposes would not be negatively affected by seasonal variation. The 4 divisions of the wheat-belt identified in this research support the use of environmentally focused classification boundaries. In addition to improving the capacity to segregate consistent quality, the linking of geographically separate production areas of the wheat-belt reduced the number of zones and this offers process efficiencies.